Butyric acid production from lignocellulosic biomass hydrolysates by engineered Clostridium tyrobutyricum overexpressing xylose catabolism genes for glucose and xylose co-utilization. (June 2017) - Fu, Hongxin; Yang, Shang-Tian; Wang, Minqi; Wang, Jufang; Tang, I-Ching
Graphical abstract: Highlights: C. tyrobutyricum was engineered to overexpress xylose catabolism genes. The mutant used xylose and glucose simultaneously for butyrate production. Undetoxified hydrolysates of lignocellulosic biomass were used as substrates. 42.6 g/L butyrate at a productivity of 0.56 g/L·h and yield of 0.36 g/g was obtained. This provides a sustainable process for cost-effective production of butyric acid. Abstract: Clostridium tyrobutyricum can utilize glucose and xylose as carbon source for butyric acid production. However, xylose catabolism is inhibited by glucose, hampering butyric acid production from lignocellulosic biomass hydrolysates containing both glucose and xylose. In this study, an engineered strain of C. tyrobutyricum Ct-pTBA overexpressing heterologous xylose catabolism genes ( xylT, xylA, and xylB ) was investigated for co-utilizing glucose and xylose present in hydrolysates of plant biomass, including soybean hull, corn fiber, wheat straw, rice straw, and sugarcane bagasse. Compared to the wild-type strain, Ct-pTBA showed higher xylose utilization without significant glucose catabolite repression, achieving near 100% utilization of glucose and xylose present in lignocellulosic biomass hydrolysates in bioreactor at pH 6. About 42.6 g/L butyrate at a productivity of 0.56 g/L·h and yield of 0.36 g/g was obtained in batch fermentation, demonstrating the potential of C. tyrobutyricum Ct-pTBA for butyric acid production from lignocellulosic biomass hydrolysates.